2022
DOI: 10.4103/sjmms.sjmms_357_21
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs, Attitudes, and Behaviors of Saudi Physiotherapists Toward Evidence-Based Practice

Abstract: Background Evidence-based practice (EBP) has gained significant importance in clinical practice worldwide, including physiotherapy, but there are limited studies that have assessed the knowledge, attitude, and behaviors of Saudi physiotherapists toward EBP. Objective: To determine the beliefs, attitudes, knowledge, and experience of Saudi physiotherapists in public hospitals of the Eastern Province of Saudi Arabia toward EBP as well as identify barriers that limit the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 22 publications
4
10
1
Order By: Relevance
“…A number of previous studies have reported positive attitudes of physiotherapists in Saudi Arabia regarding EBP and its implementation [ 24 , 25 , 26 ]; however, no studies exploring EBP and Saudi paediatric physiotherapy have been completed to date. In 2017, a survey of 376 physiotherapists found most respondents did not receive formal EBP training (70%) in universities or any other authorised training centres [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous studies have reported positive attitudes of physiotherapists in Saudi Arabia regarding EBP and its implementation [ 24 , 25 , 26 ]; however, no studies exploring EBP and Saudi paediatric physiotherapy have been completed to date. In 2017, a survey of 376 physiotherapists found most respondents did not receive formal EBP training (70%) in universities or any other authorised training centres [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the adoption of EBP is challenging for nurses in KSA and other nearby nations, including Jordan, Oman, and Iran, owing to a lack of support and implementation hurdles for EBP [ 13 ]. Therefore, the implementation of EBP and training on identified barriers is mandatory and should be considered by policymakers [ 14 ]. Online education, especially during vocational training, is one of the major ways to increase learners’ EBP competency and, as a result, promote EBP in service organizations [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the previous conducted studies in Saudi Arabia, 10,14,19,20,24 this study investigated the 6-domain of the EBP, which makes it more comprehensive than those studies that studied specific domains without paying enough attention to other domains such as attention to literature and information availability. Therefore, the current study's findings can be relied upon more than others in making the necessary decisions to enhance EBP implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Physiotherapists in several nations have been polled using this questionnaire. [21,[25][26][27][28] The 6-domain were covered in the following order: EBP-related attitudes and beliefs (questionnaire items 1-9), interest in and motivation to engage in EBP (items 10 and 11), availability of information (items [15][16][17][18][19][20], educational background, knowledge and skills related to accessing and interpreting information (items [21][22][23][24][25][26][27], and perceived barriers to using evidence in practice (survey item 28). The majority of the items covering attitudes and beliefs, education, knowledge, and abilities pertinent to EBP were assessed using a 5-point Likert scale with the anchors "strongly disagree" and "strongly agree."…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation